A Case Report of Tuberculosis with Extrapulmonary Manifestations - S Gazeran; M Emami; F Zemorshidi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2019)
BACKGROUND AND OBJECTIVE: Mycobacterium tuberculosis affects millions of people in the world and Iran is one of the endemic areas. This disease has a wide range of manifestations, which is pulmonary in 80 – 85% of cases and extrapulmonary in 15 – 20% of cases. The most notable extrapulmonary infection sites are lymph nodes, pleura, genitourinary system and digestive system. Considering the prevalence of tuberculosis in Iran, familiarity with the uncommon manifestations of this infection seems to be essential for timely diagnosis and treatment. Therefore, a rare extrapulmonary manifestation of tuberculosis is reported here. CASE REPORT: The patient was a 64 – year – old woman who was hospitalized due to fever, icterus, decreased consciousness and progressive asymmetrical weakness of the limbs. Symptoms of focal neurologic deficits and heart murmurs were found in examinations. During the tests, including brain and spinal imaging, cerebrospinal fluid analysis, computed tomography of the abdomen and pelvis, and echocardiography, extrapulmonary tuberculosis (cerebral abscess, spondylitis, liver and spleen abscess, psoas muscle abscess, and possible endocarditis) was confirmed. Four-drug regimen including isoniazid, rifampin, ethambutol, and pyrazinamide with vitamin B6 was started for two months, and two-drug regimen continued for 10 months. At the end of the course of treatment, the patient was able to walk with the cane in good general condition. CONCLUSION: Considering the reported case, paying attention to some of the more uncommon manifestations of the disease can prevent mortality and disability.